Cultures of critical spirituality to advance the inclusion of immigrant students and families in Catholic schools. Issue 3 (16th March 2022) - Scanlan, Martin
Abstract: Xenophobic, racist, and linguistically hegemonic discourses undermine the common good in our pluralistic communities. This article focuses on how these discourses adversely affect one subset of the population in the United States – those who are culturally and linguistically diverse – and how schools can disrupt this. Specifically, it explores how a culture of critical spirituality can spur systemic reform of schools to embrace cultural and linguistic diversity.